Mengenal & Memperbaiki Kualitas Tingkah Laku Interpersonal Guru - Maryatin Maryatin (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
Guru interpersonal communication can be accomplished through several ways namely through hard, soft, friend voices and joining far apart. Guru communication with students can be identified in two forms 1) dominant, and 2) cooperative. In fact, guru is more dominant than their students. There are several essential components to create effective teaching communication namely co-trustfulness, co-supportiveness, openness, sympathy, and empathy between teachers and students. Besides that, there are also essential interpersonal communication indicators namely 1) the availability of objectives that will be achieved, 2) messages as the contents of interaction, 3) students, 4) gurus, 5) methods, 6) conditions that support teaching conduct goes well and 7) evaluation.